Transcription of follicle-stimulating hormone subunit genes is modulated by porcine LIM homeobox transcription factors, LHX2 and LHX3 - YOSHIDA, Saishu; KATO, Takako; NISHIMURA, Naoto; KANNO, Naoko; CHEN, Mo; UEHARU, Hiroki; NISHIHARA, Hiroto; KATO, Yukio (Journal of Reproduction and Development, 2016)
The LIM-homeobox transcription factors LHX2 and LHX3s (LHX3a and LHX3b) are thought to be involved in regulating the pituitary glycoprotein hormone subunit genes Cga and Fshβ. These two factors show considerable differences in their amino acid sequences for DNA binding and protein-protein interactions and in their vital function in pituitary development. Hence, we compared the DNA binding properties and transcriptional activities of Cga and Fshβ between LHX2 and LHX3s. A gel mobility shift assay for approximately 1.1 kb upstream of Cga and 2.0 kb upstream of Fshβ varied in binding profiles between LHX2 and LHX3s. DNase I footprinting revealed DNA binding sites in 8 regions of the Cga promoter for LHX2 and LHX3s with small differences in the binding range and strength. In the Fshβ promoter, 14 binding sites were identified for LHX2 and LHX3, respectively. There were alternative binding sites to either gene in addition to similar differences observed in the Cga promoter. The transcriptional activities of LHX2 and LHX3s according to a reporter assay showed cell-type dependent activity with repression in the pituitary gonadotrope lineage LβT2 cells and stimulation in Chinese hamster ovary lineage CHO cells. Reactivity of LHX2 and LHX3s was observed in all regions, and differences were observed in the 5'-upstream region of Fshβ. However, immunohistochemistry showed that LHX2 resides in a small number of gonadotropes in contrast to LHX3. Thus, LHX3 mainly controls Cga and Fshβ expression.